Dinamika Korupsi dan Dampaknya Pada Pembangunan Nasional - Dian Aulia; Risa Amalia; Tarisya Arliani Munandar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article discusses the dynamics of corruption and its impact on national development. Through a comprehensive review of the factors that influence the spread and intensity of corruption, as well as its impact on various development sectors, this article illustrates the complexity of the problem of corruption in the context of national development. The negative impact of corruption is not only limited to economic losses, but also damages social order, harms public trust in the government, and hinders sustainable economic growth. By understanding the dynamics of corruption thoroughly, it is hoped that effective strategies can be formulated to combat corruption and encourage sustainable and inclusive national development.